(untitled) (International Journal of Innovative Research in Computer Science & Technology, 2022)
The data warehouse enables information to be organized in order to ease data handling from one sphere to the other and to promote knowledge acquisition. The requirement for a consistent organization and compatibility across various data sources grows as the quantity of data grows, making it more difficult to conduct thorough analyses within short periods. This study offers a trip data warehouse that uses dimensional modeling to promote a more comprehensible structure, comparable findings, quicker data access, and faster publishing of summaries. The use of multivariate representation to transport information helps to improve construction while also integrating, augmenting, and improving data. It performs data processing and validation in an automated manner. The development of transportation planning tools is anticipated to lead to the creation of a multivariate representation for trip data. In future, there is a pragmatic scope of extensive research in this field.